A spiritualitás változása lelkigondozói segítő kapcsolatokban: longitudinális hatásvizsgálat - Veronika BÓNÉ; Bernadett ASZTALOS; Beáta DÁVID; Zsolt SIPOS; Zsuzsanna SZABÓ-JÁKI; Gábor Pál TÖRÖK (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Changes in Spirituality within Pastoral Counselling Relationships: A Longitudinal Impact Study. This publication presents an impact study among clients and counsellors of two pastoral counselling centres in Hungary (one in the countryside and one in Budapest). The aim is to explore how theistic spirituality changes during the process of pastoral counselling and how this change is associated with the resolution of the problem that precedes the claim of initiating the helping relationship. The data collection took place between 2021 and 2024, the first data collection being carried out among the prospective clients who completed an online, anonymous, and voluntary questionnaire, while after the closure of the pastoral counselling process both clients and their counsellors evaluated the process (N = 55/50). Our results show that in the vast majority of cases, there has been an improvement in the initial problems, and both the clients and the helpers strongly associate this improvement with the counselling process. In parallel, theistic spirituality (measure: TSOS-HU) also increased, mainly due to a higher score in the “Love of Self” subscale.